A randomised controlled trial of the effect of a head-elevation pillow on intrathecal local anaesthetic spread in caesarean section. Issue 4 (November 2015) - Elfil, H.; Crowley, L.; Segurado, R.; Spring, A.
Highlights The effects of a head-elevation pillow during neuraxial anaesthesia were assessed. The head-elevation pillow significantly reduced intrathecal local anaesthetic spread. The head-elevation pillow effect remains when controlling for body mass index. Efforts are required to counteract this effect without recourse to higher doses.